Indian monsoon variability during the past ∼8.5 cal kyr as recorded in the sediments of the northeastern Arabian Sea - Ravichandran, M.; Gupta, Anil K.; Mohan, K.; Tiwari, Sameer K.; Lakshumanan, C.; Panigrahi, M.K. (Quaternary International, 2022)
We analyzed benthic and planktic foraminifera, total organic carbon and stable isotopes ratios of carbon and oxygen from 100 samples of marine sediment Core ABP, 25/03, off Gujarat in the northeastern Arabian Sea. Factor and cluster analyses of thirty highest-ranked benthic foraminifer species enabled to identify seven biofacies in the study sequence characterizing major changes in deep-sea environments during the past ∼8.5 cal kyr. The benthic foraminiferal data has been combined with population abundances of upwelling indicator planktic foraminifer Globigerina bulloides and mixed layer species from Core ABP, 25/03 and compared with that from ODP Hole 723A and Core ABP, 25/02, western and eastern Arabian Sea, respectively. A major change in benthic foraminifera occurs during ∼8.5 to 6 cal kyr BP, when the summer monsoon was stronger whereas during 6 to 2 cal kyr BP, the data suggest a weak summer monsoon. Planktic foraminifer Globigerina bulloides does not show any significant trend in the study core, but deep thermocline species Neogloboquadrina dutertrei and mixed layer species show significant trend with an inverse correlation with the TOC. This core records high TOC from ∼6.5 to 4 cal kyr BP and during the last 2 cal kyr and low TOC during ∼8.5 to 6.5 cal kyr BP and 4 to 2 cal kyr BP. It is interesting to note intervals of high mixed layer species coincide with high Neogloboquadrina dutertrei percentages and low TOC values at Core ABP, 25/03 during 8.5 to 6.5 cal kyr BP.The faunal data is supported by carbon and oxygen isotope ratios (δ13C and δ18O) of shells of benthic foraminifer Cibicides spp. to strengthen our understanding of changes in the eastern Arabian Sea since ∼8.5 cal kyr BP.

Response of shallow-sea benthic foraminifera to environmental changes off the coast of Goa, eastern Arabian Sea, during the last ∼6100 cal yr BPAbstract - Saravanan, Ponnusamy; Gupta, Anil K.; Zheng, Hongbo; Panigrahi, Mruganka K.; Tiwari, Sameer K.; Rai, Santosh K.; Prakasam, Muthusamy (Geological Magazine, 2020)
We have analysed a 6100-year record of benthic and planktonic foraminifera from inner neritic sediments from Core SK291/GC13, off the Goa coast, eastern Arabian Sea, to understand the response of benthic foraminifera to shallow-marine processes. The benthic foraminiferal assemblage is dominated by Nonion cf. asterizans, Ammonia beccarii, A. gaimardii and Virgulinella fragilis, which have been selected on the basis of a population of 10% or more in any three samples analysed. The planktonic foraminiferal population is sporadic and rare, with Globigerinoides ruber as the predominant species showing a variable trend. The foraminiferal proxies combined with total organic carbon (wt%) and δ13C and δ18O values of Ammonia gaimardii suggest distinct variations, indicating changes in productivity and salinity in the shallow eastern Arabian Sea. The coastal waters off Goa were relatively warmer and less saline between 6100 and 4600, or perhaps to 4200, calibrated years before the present (cal yr BP), corresponding to a stronger monsoon in South and East Asia. The shallow sea was cooler from ~4200 to 2600 cal yr BP in the study area, coinciding with a lower sea surface temperature in the northeastern Arabian Sea and an arid phase in the Indian subcontinent. From 2900 to 2600 cal yr BP the study core exhibits the impacts of short-term cold events, which have earlier been observed in the northeastern Arabian Sea, off Pakistan. During the Little Ice Age, the shallow sea off Goa was less productive.
Keywords: arabian sea; benthic foraminifera; Indian monsoon; Stable isotopes; western continental margin of India